Analyzing Tax Morale: The Influence of Socioeconomic, Job Performance, Tax Officer Job and Tax Knowledge - Nurul Laili Murfiqoh; Diah Amalia (E-Jurnal Akuntansi, 2026)
The purpose of research to examine the influence of socioeconomic factors, job performance, tax officer roles, and tax knowledge on tax morale. The research uses a quantitative method and the research sample used a simple random sampling method. The research data were collected through the distribution of 100 questionnaires to MSME entrepreneurs in Batam City. Data analysis this research by multiple linear regression using SPSS software. The findings reveal that among the four independent variables job performance, tax officer roles and tax knowledge, were found to significantly influence the tax morale of MSME in Batam City. Conversely, the socioeconomic variable, which includes age, gender, religion, education level, marital status, and work experience, showed no significant effect on tax morale. This indicates that differences in individual characteristics are not the primary determinants in shaping tax morale within the MSME in Batam City.